ChemInform Abstract: Access to Nitriles from Aldehydes Mediated by an Oxoammonium Salt. Issue 31 (August 2015) - Kelly, Christopher B.; Lambert, Kyle M.; Mercadante, Michael A.; Ovian, John M.; Bailey, William F.; Leadbeater, Nicholas E.
Abstract The spent oxidant can be recovered and regenerated.